High-performance thermoelectrics from cellular nanostructured Sb2Si2Te6 - Luo, Yubo (2020)
Thermoelectric materials promise to create additional efficiencies in energy management by harvesting the energy of waste heat and converting it to electricity. We introduce 2D Sb2Si2Te6 as a promising new high-performance thermoelectric material. Sb2Si2Te6 exhibits an intrinsically high thermoelectric figure of merit ZT value of ∼1.08 at 823 K. We then devise a unique cellular nanostructure by a post-synthetic reaction strategy that forms in situ Si2Te3 nanosheets, which serve as an effective barrier to heat propagation, yielding an ∼40% reduction in the already very low lattice thermal conductivity to ∼0.29 Wm−1K−1 at 823 K. The cellular nanostructure enables a very high ZT value of ∼1.65 at 823 K for this new material and a high average ZT value of 0.98 (400–823 K). We describe the novel cellular nanostructure design and a single-step chemical route to achieve it, highlighting a potentially new and effective general design strategy for achieving high thermoelectric performance.